The role of intra-organizational factors in accounting information system effectiveness / Shamsudeen Ladan Shagari, Akilah Abdullah and Rafeah Mat Saat. - Shagari, Shamsudeen Ladan; Abdullah, Akilah; Mat Saat, Rafeah (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
This study examines the influence of intra-organizational factors on Accounting Information System (AIS) effectiveness in Nigeria. These are internal organizational capabilities such as the internal control quality, training, and top management support that can significantly affect the success of AIS among the Nigerian Banks. In this study, exploratory research approach was adopted. A self-administered questionnaire was distributed to regional and branch offices of banks in Nigeria. A valid response rate of 48.4% was achieved, and the survey data were analyzed using Statistical Package for Social Sciences (SPSS) for the descriptive statistics and structural equation modeling for inferential analysis. The results of the study revealed that internal control quality and training are the most crucial factors in ensuring AIS effectiveness. The result further revealed that top management support is less important for the success of the systems. The findings suggest that banks should pay more attention to the internal control quality and training since they were found to be influencing the effectiveness of the system. Thus, when managers provide all the required in-house resources to support AIS, it would lead to the success of the system and which eventual result to realizing the full potential of their investment.